Success of three quarter crown in posterior teeth (Health Renaissance, 2011)
Introduction: This study was designed to observe the success of three quarter crown over conventional full veneer crown in the posterior teeth (premolars and molars) where there has been considerable destruction of tooth structure but with the buccal surface remaining intact. Method: A total number of 30 patients were studied. Among which 15 patients were treated with three quarter crown and rest of the 15 patients were treated with conventional full veneer crown. The specific parameters of the study were the preservation of natural tooth tissue, prevalence of secondary caries, conservation of periodontal health, esthetic, comfort and oral hygiene maintenance. After 6 Month of follow up period patient were recalled to evaluate the above mentioned parameters. Results: Among all the observations this study revealed the similar result in both group of patients. Periodontal disease and maintenance of oral hygiene was significantly associated in patient with three quarter crown, slight alteration of oral hygiene in the patient treated with full veneer crown was present. Conservation of the natural tooth structure especially buccal wall with negligible alteration in patient’s aesthetics (20%) as well as functional activities (20%) was significant for those patients with three quarter crown. Conclusion: Overall findings established that three quarter crown is equally effective for the restoration of the tooth and can be used as an alternative to conventional full veneer crown in the posterior teeth where there has been considerable destruction of tooth structure but with the buccal surface remaining intact. Keywords: Three quarter crown; conventional full veneer crown; secondary caries; periodontal disease; oral hygiene; esthetic DOI: http://dx.doi.org/10.3126/hren.v9i3.5586   HR 2011; 9(3): 173-178